Relationship Of Age And Work Experience With The Quality Of Nursing Work Life (QNWL) Nurses - Luthfatun Muthiah; Wirda Y Dulahu; Rachmawaty D Hunawa (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2022)
Quality of Nursing Work Life (QNWL) is a nurse's perception that can increase organizational commitment and effectiveness among nurses and increase nurse productivity and performance, which consists of 4 dimensions, namely Work Life-Home Life Dimensions, Work Design Dimensions, Work Context Dimensions, and Work Dimensions. The purpose of this study was to analyze the relationship between age and work experience with QNWL. This research is a type of quantitative research. The design used correlational analytics with a cross-sectional approach. The population of all nurses in the inpatient room at Prof. Dr. H. Aloei Saboe hospital is 134 nurses with a total sample is 57 respondents who were taken using the proportional stratified random sampling technique. The analysis was used in bivariate analysis using the Spearman rank test. The results of the study obtained a significant value for the age factor (? = 0.001) and the work experience factor (? = 0.007). In conclusion, there is a relationship between age and work experience with QNWL. Suggestions for the hospital to improve the nurse retention program so as to increase QNWL.